Customer Relationship Management in a fitness club – case study of IT solutions applied in a selected organization - Leśniewska, Aleksandra (Business Informatics, 2014)
This paper presents the structure of two information systems based on customer relationship management applied in a fitness club as a case study. The analysis of selected IT solutions is focused on their functions and modules which allow the maintenance of contact with the client and constant customer care. As the fitness business is actively growing in Poland, the cognitive goal of the paper is to present IT solutions applied in a selected fitness club as a proposal of how to manage a sports organization but also discuss those tools in terms of their usefulness and benefits for both sides – managers of the fitness club as well as the clients. The article also indicates probable precariousness of presented IT tools
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 4 (34), s. 66-76
Keywords: Customer Relationship Management; customer care; IT solutions; fitness club; client retention; zarządzanie relacjami z klientem; rozwiązania IT; fitness klub; retencja klientów